Un type méconnu d’église funéraire - Donabédian, Patrick (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
This essay is devoted to a type of medieval funerary churches which, although represented by about ten examples in Armenia and Georgia and in their sphere of influence, had not attracted the attention of specialists. These buildings are different from the better-known group of funerary churches with two levels, featuring a mausoleum topped with an oratory, crowned by a lantern in the shape of a small rotunda, well represented in Armenia in the first half of the 14th century (Urcadzor, Ełvard, Burtʻelašen of Noravankʻ, Kaputan). The type presented here is also a two-level funerary structure, but it is distinguished by two characteristics: A) The upper level corresponds to an ordinary church, most often of the longitudinal single-nave type, and in two (more hypothetical) cases, of a domed type; B) Special attention is given to the lower level, that of the funerary vault. The latter has three particular features: 1) Due to a targeted choice of location, it is partially embedded in the slope of the mountain; 2) It is built in a deliberately rustic masonry; 3) It is wider than the upper level and separated from it by a kind of cornice. According to currently available data, this type was created in the Taykʻ/Tao region, in the 9th-10th centuries, and then spread beyond its limits, up until the 13th-14th centuries.